十肽对变异链球菌作用的差异蛋白质组学研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2015)
OBJECTIVE: To compare the protein profiles between decapeptide-treated and untreated planktonic cells of Streptococcus mutans (S. mutans) by differential proteomic analysis to determine and identify the key proteins. METHODS: In our previous study, we investigated decapeptide (KKVVFKVKFK–NH(2)), which was a novel adenosine monophosphate. Compared with other oral pathogens tested, decapeptide had a preferential antibacterial activity against S. mutans. It also inhibited S. mutans biofilm formation and reduced the one-day developed biofilm. In the present study, we first synthesized decapeptide, and then compared the protein profiles between decapeptide-treated and untreated planktonic cells of S. mutans by two-dimensional gel electrophoresis and matrix-assisted laser desorption ionization time-of-flight mass spectrometry. We also verified different expressions of key protein enolase in the protein level. RESULTS: The results showed that decapeptide altered the protein expression of planktonic S. mutans. These proteins were functionally involved in carbohydrate degradation by glycolysis, protein folding, conjunction, transport, translation, adenosine triphosphate binding, protein binding, sequence-specific DNA binding, transcription factor activity, and two-component response regulator activity. Western blot results showed that enolase protein expression decreased obviously in decapeptide-treated cells of S. mutans. CONCLUSION: The protein expression of S. mutans significantly changed after synthetic antimicrobial decapeptide treatment, suggesting that decapeptide may present a preferential effect on oral caries by changing the expression of certain key proteins, such as enolase protein.